ARCHETYPAL ANALYSIS IN THE SCHOOL FOR GOOD AND EVIL NOVEL BY SOMAN CHAINANI - Arneta Putri Nurani; Dina Amelia (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2023)
This research focuses on the categories and description of archetypes that exist in the characters Sophie, Agatha, and Tedros in the novel The School for Good and Evil by Soman Chainani. The main purpose of this research is to find out the categories of archetypes in the characters in the novel. This study applied the theoretical Carl Gustav Jung about archetype to describe and analyze the characters. This research was applying a qualitative descriptive method. The data source is from the novel The School for Good and Evil by Soman Chainani, while the research data is in the form of dialogues and narratives. The result of this analysis shows that there are four categories of archetypes contained in the novel, namely persona, shadow, animus, and hero which are found by three characters in the novel namely Sophie, Agatha, and Tedros. Sophie’s character has two persona archetypes, three shadow archetypes, and one hero archetype in her. The Agatha’s character has one persona archetype, three animus archetypes, and one hero archetype. Meanwhile, the Tedros’s character only has one archetype hero in him.Keywords: Archetypes, characters, Jung analysis, novel, psychology of literature